Investigating Links between Moderate-to-Vigorous Physical Activity and Self-Rated Health Status in Adolescents: The Mediating Roles of Emotional Intelligence and Psychosocial Stress - Huilin Wang; Yang Liu; Songbiao Zhang; Ziqing Xu; Jingyu Yang (MDPI AG, 2023)
Adolescence represents a crucial phase, characterized by rapid physical and mental development and numerous challenges. Physical activity plays a vital role in the mental well-being of adolescents; however, due to the prevailing educational philosophy prioritizing academic performance, adolescent participation in physical activities has yet to reach its full potential. Thus, this study aims to investigate the effects of moderate-to-vigorous physical activity on adolescents' emotional intelligence, psychosocial stress, and self-rated health status. To achieve this objective, a cluster sampling method was employed to collect data from 600 adolescents in 10 schools across five municipal districts of Changsha, China. A total of 426 valid questionnaires were returned and analyzed. Utilizing AMOS v.23, a structural equation model was constructed to validate the hypotheses. The findings reveal that moderate-to-vigorous physical activity significantly impacts adolescents' emotional intelligence and self-rated health status. Conversely, it exerts a significant negative influence on their psychosocial stress. Moreover, emotional intelligence and psychosocial stress mediate the relationship between moderate-to-vigorous physical activity and self-rated health status. In light of these results, education departments, schools, and families must embrace a paradigm shift in educational philosophies and provide robust support for adolescents to engage in moderate-to-vigorous physical activities.